1999
DOI: 10.1099/00221287-145-11-3283
|View full text |Cite
|
Sign up to set email alerts
|

Population biology of Streptococcus pneumoniae isolated from oropharyngeal carriage and invasive disease The GenBank accession numbers for the sequences of the trpA/B alleles determined in this study are AF157817 to AF157826.

Abstract: The population structure of Streptococcus pneumoniae in a sample of 134 carried antibiotic-susceptible isolates, and 53 resistant and susceptible invasive isolates, was examined using a DNA-based version of multilocus enzyme electrophoresis: multilocus restriction typing (MLRT). This involved RFLP analysis of PCR products generated from nine loci of housekeeping genes located around the pneumococcal chromosome. The combination of alleles at each of the nine loci gave an allelic profile or restriction type (RT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 40 publications
1
44
0
Order By: Relevance
“…It has been shown that trpB/A genes exhibit substantial allelic variation (Muller-Graf et al, 1999). These genes were sequenced from wild-type organisms and their capsule phase-variable derivatives to show that these mutants had arisen from the organisms used to inoculate sorbarod filters and were not contaminants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that trpB/A genes exhibit substantial allelic variation (Muller-Graf et al, 1999). These genes were sequenced from wild-type organisms and their capsule phase-variable derivatives to show that these mutants had arisen from the organisms used to inoculate sorbarod filters and were not contaminants.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been reported that the presence of pneumococcal capsule is also important for murine carriage (Magee & Yother, 2001). Although the majority of pneumococci from clinical isolates are capsulate, a previous population genetic study of pneumococcal carriage identified two pneumococcal isolates from pernasal swabs of children and one from a pernasal swab of a female human immunodeficiency virus-positive patient that were non-serotypable (Muller-Graf et al, 1999). In addition, acapsulate pneumococci have been associated with outbreaks of conjunctivitis (Ertugrul et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the wciN 6C gene is from an organism other than pneumococci and was inserted into the 6A capsule gene locus. Horizontal gene transfers between S. pneumoniae and another bacterial species have been demonstrated with antibiotic resistance genes (5,18) and have been suggested to occur for capsule gene loci because they have low GϩC content (2). The "flanking regions" are known to be critical for homologous recombination in pneumococci (21).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have described the serotype diversity among carriage pneumococcal isolates in cultures (8,11,12), to our knowledge, only two recent studies have addressed their genetic diversity (16,28). We further characterized the strains isolated from heterogeneous samples for genetic determinants involved with DNA transfer and for susceptibility to lysis by antimicrobial agents.…”
mentioning
confidence: 99%